Autonomous arm application in clinical waste management - Jankin Abdul Rahman, Aman Wong; Nur Syairah, Mohd Radi; Norhashimah, Maktar Zani; Wan Nooraqilah, Wan Abd Kadir; Fatin Izzatie, Md Shukri; Suziyana, Mat Dahan (2021)
Autonomous Arm is operated with a gesturecontrol glove through human movements. Is a robotic concept inspired from manufacturing industries used for heavy task-load in the production line. High portability with < 5kg and modular design for different use case and attachment to different robot. Customizable with different functions of control with different preferred operating system (OS). Designed to accompany human or through longdistance control in managing waste indirectly.